Syk inhibitors reduce tau protein phosphorylation and oligomerization - Tomohisa Yamaguchi; Tadanori Hamano; Kiyonao Sada; Rei Asano; Nicholas M. Kanaan; Hirohito Sasaki; Shu-Hui Yen; Yuki Kitazaki; Yoshinori Endo; Soichi Enomoto; Norimichi Shirafuji; Masamichi Ikawa; et al. (Neurobiology of Disease)
Spleen tyrosine kinase (Syk), a non-receptor-type tyrosine kinase, has a wide range of physiological functions. A possible role of Syk in Alzheimer's disease (AD) has been proposed. We evaluated the localization of Syk in the brains of patients with AD and control participants. Human neuroblastoma M1C cells harboring wild-type tau (4R0N) were used with the tetracycline off (TetOff) induction system. In this model of neuronal tauopathy, the effects of the Syk inhibitors—BAY 61–3606 and R406—on tau phosphorylation and oligomerization were explored using several phosphorylated tau-specific antibodies and an oligomeric tau antibody, and the effects of these Syk inhibitors on autophagy were examined using western blot analyses. Moreover, the effects of the Syk inhibitor R406 were evaluated in vivo using wild-type mice. In AD brains, Syk and phosphorylated tau colocalized in the cytosol. In M1C cells, Syk protein (72 kDa) was detected using western blot analysis. Syk inhibitors decreased the expression levels of several tau phosphoepitopes including PHF-1, CP13, AT180, and AT270. Syk inhibitors also decreased the levels of caspase-cleaved tau (TauC3), a pathological tau form. Syk inhibitors increased inactivated glycogen synthase kinase 3β expression and decreased active p38 mitogen-activated protein kinase expression and demethylated protein phosphatase 2 A levels, indicating that Syk inhibitors inactivate tau kinases and activate tau phosphatases. Syk inhibitors also activated autophagy, as indicated by increased LC3II and decreased p62 levels. In vivo, the Syk inhibitor R406 decreased phosphorylated tau levels in wild-type mice. These findings suggest that Syk inhibitors offer novel therapeutic strategies for tauopathies, including AD.